Youth Development Competencies as Predictors of Perceived Inter-Ethnic Tolerant Behaviors among Undergraduates - Yee, Wendy Mei Tien (2008)
Youth are important assets for the continuous development of a nation. Therefore, many youth development programmes have been conducted to help youth to develop. Positive youth development, an approach that emphasizes the positive aspects of youth development is based on developing their health and physical competence, personal and social competence, cognitive and creative competence, vocational competence and citizenship competence. Having these competencies are very essential especially among youth living in a multi-ethnic society, Malaysia. Therefore, to avoid conflict, there is a need to be tolerant towards different cultural, religious practices, beliefs and ethnic differences. Despite many initiatives taken by the government to ensure such positive development among the youth, inter ethnic conflict is still an issue especially with the outbreak of the Kampung Medan incident in 2001 where most of the culprits involved were youth. Thus, the focus of this study is to identify the levels of youth development competencies among the undergraduates in Malaysia. Besides, based on the Theory of Planned Behavior the occurrence of a specific behavior of a person can be predicted with the presence of attitudes, subjective norms, perceived behavioral control and behavioral intentions. Incorporating both the theory of positive youth development and Theory of Planned Behavior, this study also aimed to determine the potential predictors for perceived inter ethnic tolerant behavior and to determine the level of inter-ethnic tolerance among the undergraduates. Using a self administered questionnaire, data were collected from 1086 undergraduates. Analysis was conducted to compare between undergraduates from the Public (PuIHE) and Private Institution of Higher Learning (PrIHE) and from five different programs of studies; namely, Bioscience, Social Science, Business Studies, Technical Studies and Information Technology Studies. The results indicated that students from both the institution of higher learning and across the five programs of study have the highest level of strength in vocational competence. In order to determine the predictor variables for inter ethnic tolerant behavior, a four predictors multiple linear regression model was used. The findings of this study indicated that there was a difference in prediction variables for inter-ethnic tolerant behavior between the PuIHE and PrIHE undergraduates. The results also indicated that not all the youth development competencies explained significantly to inter ethnic tolerant behavior (IETB) among students from the different programs of studies. However, among all the four youth development competencies, cognitive competence was the strongest estimator of inter ethnic tolerant behavior for the four out of five different programs of study. Overall, the model developed for this study based on the two main theories; youth development competencies and Theory of Planned Behavior on the prediction of behavior, was able to explain the gap in predicting inter ethnic tolerant behaviors among the youth.